KEPEMIMPINAN KEPALA SEKOLAH DIMASA PTMT DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA - Lia Pertiwi; Syafriyana Ritonga; M. Joharis Lubis; Tappil Rambe (Sekolah Tinggi Pariwisata Mataram, 2022)
The principal's leadership in leading in limited face-to-face learning situations has guidelines for increasing student learning enthusiasm. To increase students' learning motivation, teachers are also responsible for guiding and increasing students' learning motivation and the role of students' parents is also inseparable from mentoring so that the goals and expectations for generations of students are expected to be achieved. The principal is the person closest to the teacher both in planning and in the learning process and has an important influence on the environmental situation at school. The purpose of this article is to discuss the improvement in student learning with the motivation of the principal during the PTMT (limited face-to-face learning) period today so that students are more enthusiastic, more active, and creative in carrying out learning at school.